(untitled) (SCIENCE TIME JOURNAL, 2025)
Zoonyms, or animal names, serve as crucial linguistic elements that provide insight into the intricate relationship between language and culture. This article investigates the cultural connotations, symbolic meanings, and idiomatic expressions associated with zoonyms. The findings reveal that zoonyms embody societal beliefs, values, and environmental interactions, functioning as cultural artifacts that shape identities and worldviews. Additionally, the study examines the impact of globalization on the evolution of zoonyms within increasingly interconnected linguistic landscapes. The article emphasizes the importance of zoonyms in understanding cultural narratives and cognitive frameworks.